Environmental pollution and allergies - Takano, Hirohisa (J Toxicol Pathol, 2017)
Environmental changes are thought to be the main factor in the rapid increase and worsening of allergic diseases. While there have been significant changes in many environmental factors, including in environments such as residential, health and sanitation, food, and water/soil/atmospheric environments, the root of each of these changes is likely an increase in chemical substances. In fact, various environmental pollutants, such as air pollutants and chemical substances, have been shown to worsen various allergies in experimental studies. For example, diesel exhaust particles (DEPs), which are an agglomeration of particles and a wide array of chemical substances, aggravate asthma, primarily due to the principle organic chemical components of DEPs. In addition, environmental chemicals such as phthalate esters, which are commonly used as plasticizers in plastic products, also aggravate atopic dermatitis. It has also become evident that extremely small nanomaterials and Asian sand dust particles can enhance allergic inflammation. While the underlying mechanisms that cause such aggravation are becoming clearer at the cellular and molecular levels, methods to easily and quickly evaluate (screen) the ever-increasing amount of environmental pollutants for exacerbating effects on allergies are also under development. To eliminate and control allergic diseases, medical measures are necessary, but it is also essential to tackle this issue by ameliorating environmental changes.